2020
DOI: 10.14504/ajr.7.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Durable Press Finishing of Cotton Fabric with BTCA by Response Surface Methodology

Abstract: Durable press (DP) finishing process of cotton fabric with 1,2,3,4-butanetetracarboxylic acid (BTCA) was investigated and optimized using the Box-Behnken design (BBD) with a response surface methodology (RSM). BBD experimental data were fitted to create the response surface regression models describing wrinkle recovery angle (WRA) and breaking strength of the finished cotton fabric. Analysis of variance (ANOVA) revealed that the concentration of BTCA was the most significant variable affecting the WRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A possible cross-linking pathway is presented in Scheme 2. The results indicated that there was a coupling effect between BTCA and CA and the fabrics treated with the combination of BTCA (50 g/L) and CA (about 40 g/L) displayed a compromised WRA and tensile strength, which was consistent with our previous report [29]. In addition, using mixed polycarboxylic acids also has an advantage of decreasing the yellowness of the treated Table 2, possibly, partially due to the reaction of hydroxyl groups of CA to the carboxylic acid groups in BTCA and inhibiting formation of unsaturated aconitic acid [22,31].…”
Section: Mechanism Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…A possible cross-linking pathway is presented in Scheme 2. The results indicated that there was a coupling effect between BTCA and CA and the fabrics treated with the combination of BTCA (50 g/L) and CA (about 40 g/L) displayed a compromised WRA and tensile strength, which was consistent with our previous report [29]. In addition, using mixed polycarboxylic acids also has an advantage of decreasing the yellowness of the treated Table 2, possibly, partially due to the reaction of hydroxyl groups of CA to the carboxylic acid groups in BTCA and inhibiting formation of unsaturated aconitic acid [22,31].…”
Section: Mechanism Analysissupporting
confidence: 92%
“…For investigating the kinetics, the finishing solutions of (i) a BTCA/CA system containing 50 g/L of BTCA, 45 g/L of CA, and 38 g/L of SHP and (ii) a BTCA system containing 73 g/L of BTCA and 38 g/L of SHP were used to treat the fabrics. These two formulas were the best formula obtained, to optimize the wrinkle resistance and strength retention, in our previous work [32,33].…”
Section: Fabric Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that this resin-finishing process's operational parameters might influence end-use performance [ 30 ]. As mentioned earlier, Taguchi's design was employed for the resin-finishing process using important parameters, including the concentration of resin, softener, catalyst, curing temperature, and time, which are nonlinear.…”
Section: Resultsmentioning
confidence: 99%